CORRELATION ANALYSIS OF THE INTEGRAL THE FITNESS OF GYMNASTS 12-17 YEARS OLD - Narzievich, Umarov Mars; Samijonovich, Tajibaev Soyib; Bakhtiyorjonovna, Sanokulova Zamirajon (The journal of contemporary issues in business and government, 2021)
The materials of the correlation analysis allowed us to study the peculiarities of the connection of various aspects of the integral fitness of gymnasts with their sports and technical skills. The ma- trix of the 20th order was analyzed by the method of the main components, which includes the main indicators characterizing the training process of young gymnasts aged 12-17 years.